Leukemia cutis: a rare manifestation of an underlying primary plasma cell leukemia - Dixit, Nutan; Trivedi, Shalini; Bansal, Vikas Kumar; Jain, Pooja; Raina, Aditi; Agarwal, Sonal (Journal of Pathology of Nepal, 2023)
Plasma cell leukaemia is the rarest yet most aggressive plasma cell disorder characterized by a malignant proliferation of plasma cells in the blood and bone marrow. Leukaemia cutis includes cutaneous manifestation of any type of leukaemia, and is defined as skin infiltration by malignant leukocytes or their precursors, resulting in clinically detectable cutaneous lesions. Plasma cell leukaemia cutis is a rare clinical presentation with an adverse prognosis which makes the index case an unusual entity. We hereby report a case of primary Plasma cell leukaemia, who presented with multiple cutaneous scalp nodules. Fine needle aspiration cytology performed on these scalp nodules revealed cellular smears exhibiting mature and immature plasma cells dispersed singly and arranged in small clusters. The total leukocyte count was 25,800/cu mm, with differential count of 18% polymorphonuclear leukocytes, 20% lymphocytes and 62% abnormal plasmacytoid cells. The diagnosis of primary PCL with cutaneous involvement was subsequently rendered through histology and immunophenotyping.